Taxonomic analysis of the genital plates and associated structures in Ophiuroidea (Echinodermata) - Stöhr, Sabine (European Journal of Taxonomy, 2024)
Recently, new insights have been gained from the ophiuroid skeleton that were instrumental in the inference of a new phylogeny. The so far least studied ossicles are the adradial and abradial genital plates and the radial shields, which articulate with each other and support the genital slit and disc. In addition, the inner sides of the oral shields and madreporites have never been examined in detail. The present study utilized SEM, micro-CT and digital photography to document and examine these structures in 57 species from 28 of the currently accepted 34 families of Ophiuroidea. Early ontogeny and fossils were also considered. Previously, mainly the articular structures had been analysed, but the overall shape of the genital plates was here found to hold important phylogenetic signals. A long-neglected ossicle was re-discovered and studied in detail for the first time, here named the oral genital plate. It was recognized in all Ophintegrida, but was found to be absent in all Euryophiurida. The oral genital plate articulates with the oral shield and supports the proximal part of the genital slit wall. Abradial and oral genital plates were found to be absent in species that lack genital slits, but the adradial genital plate was always present. Numerous new morphological characters with potential phylogenetic signals were identified, described and figured in detail. A pre-existing character matrix was extended and revised with these new data, as well as with recently revised data on oral papillae, and a Bayesian phylogenetic analysis was performed. This phylogeny largely agrees with the current molecular hypothesis, but some branches were not supported.